Inclusive Businesses as a Source of Quality Work for Small Entrepreneurs in Poverty Conditions : An Exploratory Study in the Municipality of Apartadó, Colombia - Pineda Escobar, María Alejandra (Universidad de La Salle. Revistas. Equidad & Desarrollo., 2016)
This paper develops a prefeasibility study for the implementation of inclusive businesses in the municipality of Apartadó (Colombia), being understood as business plans that link the vulnerable population to the value chain of companies in order to generate economic and social value. Thus, the purpose was to analyze, together with the key stakeholders in the area, the business planning potential in the territory in an inclusive and sustainable manner, and the possibility of consolidating new quality work alternatives for small female entrepreneurs in poverty conditions. After exploring the theoretical framework of inclusive business, the paper presents the results of interviews and focus groups, as well as the main conclusions and suggestions for future research.